Issues and challenges facing RTI Act - Chaudhary, Anita (2016)
Right to Information has been hailed as a path-breaking legislation of recent years. Eleven years of implementation and the Act is considered to be the best thing that could happen to good governance. Success stories abound highlighting the empowerment of the people in getting their rights and dues. However, the euphoria surrounding the Right seems to be fading. People are still filing RTIs, but the wait for a final resolution seems to be getting longer. Transparency, accountability of public authorities, reduction in corruption, people's participation in policy formulation and implementation - all objectives of the Act, seem to be moving in slow motion or just going through the motion. The attitude of all stakeholders towards effective implementation has lost the initial vigour. Public authorities do not suo motu disclose information, give out half-baked information, applicants file appeals and wait for final resolution of their balance of power is sought to be shifted in the delivery of services, anti-social elements are taking advantage either through threats to the query-raiser, or blackmailing other stakeholders in the system. In this article, some of the important challenges and issues being faced in the implementation of the Act have been discussed.queries as in a proverbial judicial process. Meanwhile, as the balance of power is sought to be shifted in the delivery of services, anti-social elements are taking advantage either through threats to the query-raiser, or blackmailing other stakeholders in the system. In this article, some of the important challenges and issues being faced in the implementation of the Act have been discussed. - Reproduced.
Keywords: Right to information